How can resilience moderate the effects of the COVID-19 pandemic on mental health? - C. Ciampi; M. Carfagno; M. Raia; V. Giallonardo; V. Del Vecchio; M. Luciano; G. Sampogna; A. Fiorillo (European Psychiatry, 2022)
Introduction The COVID-19 pandemic represents a new form of trauma, which is impacting on the mental health of the general population. However, the effects of this new trauma are variable, being mediated by individual factors such as the levels of resilience and the coping strategies.